Reticular contraction frequency and ruminal gas dome development in goats do not differ between grass and browse diets. Issue 6 (17th November 2021) - Clauss, Marcus; Tschuor, Andreas; Codron, Daryl; Hummel, Jürgen
Abstract: In investigations of differences between ruminant species feeding on browse or grass, it is often unclear whether observed differences are animal‐ or forage‐specific. Ruminant species have been classified as 'moose‐type', with little rumen content stratification, or 'cattle‐type' with a distinct rumen contents stratification, including a gas layer. To which extent putative differences in forestomach motility are involved in these patterns is unknown. Using sonography, we investigated the frequency of reticular contractions and the stratification of rumen contents in goats fed exclusively on grass hay ( n  = 6) or dried browse ( n  = 5) directly after feeding, and after another 6 and 12 h with no access to feed. The frequency of reticular contractions decreased from immediately after feeding (1.8 ± 0.3 min −1 ) to 6 h afterwards (1.2 ± 0.2 min −1 ) and then remained constant, with no difference between diets. A gas dome became more visible over time, but neither its incidence nor its extent differed between diets. The results are in accord with classifying goats as 'cattle‐type' in terms of their digestive physiology, and they add to a growing body of evidence that differences in digestive physiology between ruminant species are more due to species characteristics than different kinds of ingested forages.